Effects of exercise training on C-reactive protein (CRP) levels and 6-minute walk distance: A preliminary study - Aziz, Indra Jabbar; Martini, Heny; Anna Fuji Rahimah; Valerinna Yogibuana; Cholid Tri Tjahjono (Heart Science Journal, 2025)
Background Mortality rates increase among those with intermediate to high-risk pulmonary arterial hypertension, demonstrating the importance of improved diagnostic methods, treatment algorithms, and the development of new approaches to therapy for severely ill patients. Inflammation contributes to pulmonary hypertension progression, and exercise has been shown to suppress this process. Objective This study evaluated the relationship and differences between CRP levels and functional capacity after a 12-week exercise training program. Methods A clinical prospective cohort preliminary study was conducted with 26 consecutive patients who had already received pulmonary hypertension treatment and were enrolled in the LET-SHINE registry. Patients were divided into two groups: one control group (PH therapy only) and one treatment group (receiving adjuvant physical exercise). The study was conducted for 12 weeks, 6MWT and CRP tests were performed both before and after the study. Result This study found that the majority of cases were ASD, consistent with the fact that ASD is the most common congenital heart defect. The analysis of C-reactive protein levels showed non-significant changes in both groups after 12 weeks. The treatment group exhibited a modest reduction from 0.8 ± 2.4 mg/dl to 0.5 ± 1.0 mg/dl (p=0.514), while the control group maintained stable levels, ranging from 0.7 ± 1.0 mg/dl to 0.7 ± 0.8 mg/dl (p=0.166). An intergroup comparison revealed a non-significant greater mean decrease in the treatment group (-0.3 ± 1.5 mg/dl vs -0.1 ± 0.2 mg/dl, p=0.514). There was no significant correlation between the reduction in CRP levels and improvements in 6MWT distance in either the treatment group (correlation coefficient: -0.367, p=0.240) or the control group (correlation coefficient: 0.021, p=0.948). Conclusion This study showed that exercise training had no statistically significant impact on C-reactive protein levels, indicating a limited effect on systemic inflammation. No significant correlation was found between decreases in CRP levels and improvements in 6MWT distance in either the treatment or control groups.